A minmax extremum-seeking controller design technique. Issue 1 (July 2017) - Guay, Martin; Hudon, Nicolas
Abstract: This paper considers the solution of a minmax optimization problem for a class of unknown nonlinear systems using a perturbation-based proportional-integral extremum seeking control design technique. It is assumed that the equations describing the dynamics of the maximizing and minimizing players are unknown and the cost function to be minimized is unknown but available for measurement to both players. The proposed control system is shown to stabilize the minimizing player in the presence of destabilizing attacks. A simulation example is used to illustrate the effectiveness of the proposed technique.